Pelatihan Perancangan Model Bisnis untuk Usaha Baru dengan menggunakan BMC bagi Siswa SMA Kr. Pringadi - Yoppy Mirza Maulana (Jurnal Ragam Pengabdian, 2025)
Comprehension of business models is fundamental for the effective design and development of new ventures, particularly for students beginning to explore entrepreneurship. This community service program aimed to equip students of SMA Kristen Pringadi with the skills to develop business models using the (BMC) Business Model Canvas framework. The training was implemented in three stages: preparation, execution, and evaluation. In addition to introducing the BMC framework, the training also presented the eight types of e-business models developed by Peter Weill and Michael R. Vitale as a conceptual foundation. The effectiveness of the training was assessed by comparing the results of pre-tests and post-tests. Of the 18 participants, 9 students (50%) demonstrated improvement, 7 students (38.9%) maintained the same scores, and 2 students (11.1%) showed no improvement. These findings suggest that the training had a positive impact on most participants' understanding of business model design. It is hoped that this activity will serve as an initial step in cultivating entrepreneurial interest and competence among high school students.